The portrayal of queerness in E. M. Forster’s Maurice - Irusta, Ainoa Ingunza (2022)
Maurice, written by renowned English writer E.M. Forster, is a staple of modern queer literature. The aim of this paper is to present an analysis of the portrayal of queerness in Maurice, discussing the dynamics between societal norms of early-1900s England and homosexuality in the book. Further, this work aims to enlarge the existing corpus of research and diversify literary analysis in the academic field. The analysis was carried out by dint of queer theory, mainly through a Foucauldian lens. The methodology consisted of four steps: reading of Maurice accompanied by commentated note-taking; extensive research of previous studies; writing process; and editing and revision of the paper. The discussion and analysis showcase the portrayal of queerness as a key aspect of the material. Maurice depicts the imposition of heteronormativity and the demonization of homosexuality through law and blackmail, disgust and sinfulness, and internalized homophobia. Moreover, Maurice presents a narrative that subverts homophobic beliefs through its portrayal of queerness.